Sealing resin sheet

The sealing resin sheet with a layered structure addresses warping issues by controlling resin entry and stress, enabling precise surface processing of electronic components.

JP7601568B2Active Publication Date: 2024-12-17NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020104401
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-17
Publication Date
2024-12-17
Estimated Expiration
2040-06-17

AI Technical Summary

Technical Problem

The generation of internal stress during the curing process of sealing resin sheets leads to warping in workpieces, causing significant height differences on the surface, which hinders precise surface processing of electronic component chips.

Method used

A sealing resin sheet with specific configurations, including a first and second sealing resin layer, where the first layer contains a thermosetting resin and a layered silicate compound, and the second layer contains a thermosetting resin and an inorganic filler, is designed to suppress internal stress and warping, ensuring precise surface processing.

Benefits of technology

The resin sheet effectively controls the entry of resin into gaps between components, prevents warping and damage during manufacturing, and allows for high-precision surface processing, such as laser printing, by maintaining viscosity and suppressing excessive intrusion into voids.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601568000004
    Figure 0007601568000004
  • Figure 0007601568000005
    Figure 0007601568000005
  • Figure 0007601568000006
    Figure 0007601568000006
Patent Text Reader

Abstract

To provide a sealing-resin sheet suitable for machining the surface of a sealing resin for sealing an electronic component chip with good precision in a manufacturing process of a resin seal body of the electronic component chip mounted on a substrate.SOLUTION: A sealing-resin sheet X according to the present invention comprises a thermosetting resin. The sealing-resin sheet is 80% or larger in warp-recovery R given by the formula (1) below in a warp-recovery evaluation test arranged to perform a predetermined first treatment, a first measurement, a second treatment and a second measurement in this order. Formula (1): R=[(D1-D2) / D1]×100.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an encapsulating resin sheet. [Background technology]

[0002] Conventionally, electronic component chips such as semiconductor chips mounted on a mounting substrate are sometimes sealed on the substrate by a sheet-like sealing resin material (sealing resin sheet) containing a thermosetting resin to manufacture a resin-sealed body of electronic component chips. In the sealing process, for example, a sealing resin sheet of a predetermined thickness is pressed in a heated and softened state by a flat press machine against a plurality of electronic component chips bonded to the same surface of a substrate and spaced apart from each other, and the sheet is plastically deformed to cover each electronic component chip (pressing process). Then, the sealing resin sheet covering the electronic component chips is hardened by heating at a high temperature (hardening process). After this, the hardened sealing resin sheet is cut along a predetermined cutting line by, for example, blade dicing, and each resin-sealed body is individually divided. A technology related to the resin sealing of electronic component chips by a sealing resin sheet is described, for example, in the following Patent Document 1. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-220350 A Summary of the Invention [Problem to be solved by the invention]

[0004] Internal stress occurs in the encapsulating resin sheet (encapsulating resin material) that is heat-cured in the curing process. This internal stress may cause warping in the workpiece (e.g., a substrate on which multiple electronic component chips are encapsulated by the encapsulating resin sheet) obtained through the curing process. The larger the workpiece size, i.e., the larger the encapsulating resin sheet used, the greater the height difference that occurs on the workpiece surface due to the warping of the workpiece. If the height difference on the workpiece surface is too large, it is not possible to perform surface processing such as laser marking, which is performed on the encapsulating resin surface for each electronic component chip in the workpiece, with high accuracy over the entire workpiece.

[0005] The present invention provides an encapsulating resin sheet suitable for precisely processing the surface of an encapsulating resin that encapsulates an electronic component chip in a process for producing a resin-encapsulated body of an electronic component chip mounted on a substrate. [Means for solving the problem]

[0006] The present invention [1] is an encapsulating resin sheet containing a thermosetting resin, and includes an encapsulating resin sheet having a warp recovery rate R of 80% or more, as shown in the following formula (1), in a warp recovery evaluation test in which the following first treatment, first measurement, second treatment, and second measurement are carried out in this order.

[0007] First treatment: A laminate sample comprising a 42 alloy plate measuring 90 mm x 90 mm x 150 μm thick and the sealing resin sheet bonded to the entire surface of one side of the 42 alloy plate in the thickness direction is heated at 150°C for 1 hour and then allowed to stand at 25°C for 1 hour. First measurement: The maximum distance between the surface on which the laminate sample is placed with the 42 alloy plate of the laminate sample facing down and the edge of the laminate sample is measured as the first warping length D1. Second treatment: The laminate sample is placed on the surface of a heating plate at 100° C. for 1 minute. Second measurement: The maximum distance between the surface of the heating plate and the edge of the laminate sample is measured as a second warpage length D2.

[0008] Formula (1): R=[(D1-D2) / D1]×100

[0009] A configuration in which the warp recovery rate R shown in the above-mentioned warp recovery evaluation test is 80% or more is suitable for precisely processing the encapsulating resin surface by suppressing the height difference on the work surface during the manufacturing process of an electronic component chip resin encapsulating body in which the encapsulating resin sheet is used.

[0010] The present invention [2] includes the encapsulating resin sheet according to the above [1], in which the second warpage length D2 is 2 mm or less.

[0011] Such a configuration is suitable for precisely processing the encapsulating resin surface in the process of producing an electronic component chip resin-encapsulated body in which the encapsulating resin sheet is used.

[0012] The present invention [3] includes the sealing resin sheet according to the above [1] or [2], wherein the sealing resin sheet includes a first sealing resin layer and a second sealing resin layer in that order in a thickness direction, the first sealing resin layer contains a first thermosetting resin and a layered silicate compound, and the second sealing resin layer contains a second thermosetting resin.

[0013] The present encapsulating resin sheet having such first and second encapsulating resin layers can be used to encapsulate, for example, an electronic component chip mounted on a substrate in a state of facing the substrate with a gap therebetween, through the following pressing and curing steps. In the pressing step, the present encapsulating resin sheet is pressed toward the substrate while being heated and softened in a state where the first encapsulating resin layer side of the present encapsulating resin sheet is in contact with the electronic component chip on the substrate (the open edge of the gap is closed by the first encapsulating resin layer that is in close contact with the substrate around the electronic component chip). In such a pressing step, the present encapsulating resin sheet is suitable for the first encapsulating resin layer together with the second encapsulating resin layer to soften and flow under the pressing force and deform to follow the outer shape of the electronic component chip (the configuration in which the first encapsulating resin layer contains a layered silicate compound is suitable for increasing the viscosity of the first encapsulating resin layer and for expressing thixotropic properties in which the viscosity of the first encapsulating resin layer is lower when the first encapsulating resin layer is subjected to a pressing force than when the first encapsulating resin layer is not subjected to a pressing force). In the curing step after the pressing step, the encapsulating resin sheet covering the electronic component chip is further heated and cured. Since the first encapsulating resin layer contains a layered silicate compound, the viscosity reduction caused by the temperature increase is suppressed in the curing step, and excessive penetration into the gap is suppressed (in contrast, the viscosity of the second encapsulating resin layer is reduced once before curing and becomes fluid, and the exposed surface on the opposite side to the first encapsulating resin layer is flattened). In other words, the encapsulating resin sheet is suitable for controlling the penetration length of the encapsulating resin into the gap between the substrate and the electronic component chip in the manufacturing process of the electronic component chip resin encapsulation body.

[0014] The present invention [4] includes the encapsulating resin sheet according to the above [3], in which the penetration length L shown in a penetration length evaluation test in which the following first to fourth steps are carried out is 0 μm or more and 50 μm or less.

[0015] First step: A dummy chip mounting substrate is prepared, the substrate comprising a glass substrate and a dummy chip measuring 3 mm x 3 mm x 200 μm thick, the dummy chip being bonded to the glass substrate via bumps in a state facing the glass substrate with a gap therebetween, and the length from the glass substrate to the dummy chip in the gap being 20 μm. Second step: With the first sealing resin layer side of the sealing resin sheet in contact with the dummy chip on the glass substrate, the sealing resin sheet is pressed toward the glass substrate using a vacuum platen press under conditions of a temperature of 65°C, a vacuum degree of 1.6 kPa or less, a pressure of 0.1 MPa, and a pressure time of 40 seconds, and the open edge of the gap is sealed by the first sealing resin layer that is in close contact with the glass substrate around the dummy chip. Third step: After the second step, the sealing resin sheet is cured by heating at 150° C. under atmospheric pressure for 1 hour. Fourth step: After the third step, the penetration length L of the sealing resin sheet into the gap is measured.

[0016] A configuration in which the penetration length L shown in the above penetration length evaluation test is 0 μm or more and 50 μm or less is suitable for controlling the penetration length of the encapsulating resin into the gap between the substrate and the electronic component chip in the manufacturing process for an electronic component chip resin encapsulation body, which includes the pressing process and curing process as described above, in which this encapsulating resin sheet is used.

[0017] The present invention [5] includes the sealing resin sheet according to the above [3] or [4], wherein the first sealing resin layer has a first tensile storage modulus of 3.5 GPa or more at 25°C after heat treatment at 150°C for 1 hour.

[0018] Such a configuration is suitable for suppressing damage such as cracks and chipping from occurring in the substrate on which the electronic component chip is mounted when the substrate is singulated by blade dicing during the manufacturing process of an electronic component chip resin-sealed body in which the present encapsulating resin sheet is used.

[0019] The present invention [6] includes the encapsulating resin sheet according to any one of the above [3] to [5], wherein the second encapsulating resin layer has a glass transition temperature of 100°C or lower after heat treatment at 150°C for 1 hour.

[0020] Such a configuration is suitable for reducing warping of the encapsulating resin sheet when the encapsulating resin sheet is warped after being heat-cured by temporarily softening the encapsulating resin sheet by heating at about 100°C.

[0021] The present invention [7] includes the sealing resin sheet according to any one of the above [3] to [6], wherein the second sealing resin layer has a second tensile storage modulus of 0.5 GPa or less at 100°C after heat treatment at 150°C for 1 hour.

[0022] Such a configuration is suitable for reducing warping of the encapsulating resin sheet when the encapsulating resin sheet is warped after being heat-cured by temporarily softening the encapsulating resin sheet by heating at about 100°C.

[0023] The present invention [8] includes the sealing resin sheet according to any one of the above [1] to [4], in which a ratio of a second tensile storage modulus at 100°C of the second sealing resin layer after heat treatment at 150°C for 1 hour to a first tensile storage modulus at 25°C of the first sealing resin layer after heat treatment at 150°C for 1 hour is 0.12 or less.

[0024] Such a configuration is suitable for achieving both the suppression of the warping and the suppression of the damage described above. [Brief description of the drawings]

[0025] [Figure 1] 1 is a schematic cross-sectional view of an embodiment of an encapsulating resin sheet of the present invention. FIG. [Diagram 2]This shows a method for encapsulating electronic component chips on a substrate using the encapsulating resin sheet shown in Fig. 1. Fig. 2A shows a process for preparing the encapsulating resin sheet, Fig. 2B shows a process for placing a workpiece and the encapsulating resin sheet between the press plates of a flat press machine, Fig. 2C shows a pressing process, and Fig. 2D shows a curing process. [Diagram 3] 3 shows an evaluation test of the penetration length in the examples and the comparative examples, in which Fig. 3A shows a process of preparing an encapsulating resin sheet, Fig. 3B shows a process of placing a workpiece and an encapsulating resin sheet between press plates of a flat press machine, Fig. 3C shows a pressing process, and Fig. 3D shows a curing process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The encapsulating resin sheet X is a sheet-like encapsulating resin material for encapsulating electronic component chips such as semiconductor chips, and includes a first encapsulating resin layer 11 and a second encapsulating resin layer 12 in that order in the thickness direction. The encapsulating resin sheet X preferably includes only the first encapsulating resin layer 11 and the second encapsulating resin layer 12 located on one surface of the first encapsulating resin layer 11 in the thickness direction.

[0027] The first sealing resin layer 11 is a layer formed from a thermosetting composition (first thermosetting composition), and in this embodiment, contains at least a thermosetting resin and a layered silicate compound, and may contain an inorganic filler (first inorganic filler). The first sealing resin layer 11 is in an uncured state (A stage state) or a semi-cured state (B stage state).

[0028] Examples of the thermosetting resin include epoxy resin, silicone resin, urethane resin, polyimide resin, urea resin, melamine resin, and unsaturated polyester resin. These thermosetting resins may be used alone or in combination of two or more. The content of the thermosetting resin in the first thermosetting composition is preferably 10% by mass or more, more preferably 15% by mass or more. The content of the thermosetting resin in the first thermosetting composition is preferably 50% by mass or less, more preferably 40% by mass or less.

[0029] As the thermosetting resin, an epoxy resin is preferably used. The epoxy resin is prepared, for example, as an epoxy resin composition containing a base resin, a curing agent, and a curing accelerator.

[0030] Examples of the base agent include bifunctional epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, modified bisphenol A type epoxy resin, modified bisphenol F type epoxy resin, and biphenyl type epoxy resin, and trifunctional or more polyfunctional epoxy resins such as phenol novolac type epoxy resin, cresol novolac type epoxy resin, trishydroxyphenylmethane type epoxy resin, tetraphenylolethane type epoxy resin, and dicyclopentadiene type epoxy resin. These base agents may be used alone or in combination of two or more. As the base agent, a bifunctional epoxy resin is preferably used, and more preferably at least one selected from the group consisting of bisphenol A type epoxy resin and bisphenol F type epoxy resin is used.

[0031] The epoxy equivalent of the base material is, for example, 10 g / eq. or more, and preferably 100 g / eq. or more. The epoxy equivalent of the base material is, for example, 500 g / eq. or less, and preferably 450 g / eq. or less.

[0032] The softening point of the base is preferably 50° C. or higher, more preferably 60° C. or higher, even more preferably 72° C. or higher, and particularly preferably 75° C. or higher. The softening point of the base is preferably 130° C. or lower, more preferably 110° C. or lower, and even more preferably 90° C. or lower. This configuration makes it easy to mix the first thermosetting composition when preparing the composition, and also makes it easy to control the flow characteristics of the composition after mixing.

[0033] The ratio of the base material in the first thermosetting composition is, for example, 3% by mass or more, and preferably 5% by mass or more. The ratio of the base material in the first thermosetting composition is, for example, 17% by mass or less, and preferably 15% by mass or less.

[0034] As the curing agent, a phenol resin is preferably used. Examples of the phenol resin include novolac-type phenol resins such as phenol novolac resin, phenol aralkyl resin, cresol novolac resin, tert-butylphenol novolac resin, and nonylphenol novolac resin. As the curing agent, at least one selected from the group consisting of phenol novolac resin and phenol aralkyl resin is preferably used.

[0035] In the epoxy resin composition, the amount of hydroxyl groups in the phenolic resin curing agent relative to 1 equivalent of epoxy groups in the epoxy resin base is, for example, 0.7 equivalents or more, preferably 0.9 equivalents or more. Also, the amount of hydroxyl groups in the phenolic resin curing agent relative to 1 equivalent of epoxy groups in the epoxy resin base is, for example, 1.5 equivalents or less, preferably 1.2 equivalents or less.

[0036] The curing accelerator is a catalyst (thermal curing catalyst) that accelerates the curing of the base agent by heating. Examples of the curing accelerator include imidazole compounds and organic phosphorus compounds. Examples of the imidazole compounds include 2-phenyl-4,5-dihydroxymethylimidazole and 2-phenyl-4-methyl-5-hydroxymethylimidazole. Examples of the organic phosphorus compounds include triphenylphosphine, tricyclohexylphosphine, tributylphosphine, and methyldiphenylphosphine. As the curing accelerator, an imidazole compound is preferably used, and more preferably 2-phenyl-4,5-dihydroxymethylimidazole is used. The amount of the curing accelerator to be mixed with 100 parts by mass of the base agent is, for example, 0.05 parts by mass or more. The amount of the curing accelerator to be mixed with 100 parts by mass of the base agent is, for example, 5 parts by mass or less.

[0037] The layered silicate compound is a component that imparts thixotropy to the first thermosetting composition while thickening the first thermosetting composition, and is dispersed in the first thermosetting composition.

[0038] Examples of the layered silicate compound include smectite, kaolinite, halloysite, talc, and mica. Examples of the smectite include montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, and stevensite. As the layered silicate compound, smectite is preferably used, and montmorillonite is more preferably used, since it is easily mixed with the thermosetting resin.

[0039] The layered silicate compound may be an unmodified one whose surface is not modified, or may be a modified one whose surface is modified by an organic component.For example, from the viewpoint of affinity with thermosetting resin, preferably, a layered silicate compound whose surface is modified by an organic component is used, more preferably, an organically modified smectite whose surface is modified by an organic component is used, and even more preferably, an organically modified bentonite whose surface is modified by an organic component is used.

[0040] Examples of the organic component include organic cations (onium ions) such as ammonium, imidazolium, pyridinium, and phosphonium.

[0041] Examples of ammonium include dimethyl distearyl ammonium, distearyl ammonium, octadecyl ammonium, hexyl ammonium, octyl ammonium, 2-hexyl ammonium, dodecyl ammonium, and trioctyl ammonium. Examples of imidazolium include methyl stearyl imidazolium, distearyl imidazolium, methyl hexyl imidazolium, dihexyl imidazolium, methyl octylimidazolium, dioctylimidazolium, methyl dodecyl imidazolium, and didodecyl imidazolium. Examples of pyridinium include stearyl pyridinium, hexyl pyridinium, octyl pyridinium, and dodecyl pyridinium. Examples of the phosphonium include dimethyl distearyl phosphonium, distearyl phosphonium, octadecyl phosphonium, hexyl phosphonium, octyl phosphonium, 2-hexyl phosphonium, dodecyl phosphonium, and trioctyl phosphonium. The organic cation may be used alone or in combination of two or more. As the organic cation, ammonium is preferably used, and dimethyl distearyl ammonium is more preferably used.

[0042] As the organically modified layered silicate compound, preferably, an organically modified smectite whose surface is modified with ammonium is used, and more preferably, an organically modified bentonite whose surface is modified with dimethyldistearylammonium is used.

[0043] The average particle size of the layered silicate compound is, for example, 1 nm or more, preferably 5 nm or more, more preferably 10 nm or more. The average particle size of the layered silicate compound is, for example, 100 μm or less, preferably 50 μm or less, more preferably 10 μm or less. The average particle size of the layered silicate compound is, for example, determined as a D50 value (cumulative 50% median size) based on the particle size distribution determined by a particle size distribution measurement method in a laser scattering method.

[0044] As the layered silicate compound, commercially available products can be used. Commercially available organic bentonite products include, for example, the Esben series (manufactured by Hojun Co., Ltd.).

[0045] The content of the layered silicate compound in the first sealing resin layer 11 (i.e., the content of the layered silicate compound in the first thermosetting resin composition) is preferably 1.2 mass% or more, more preferably 1.5 mass% or more. The content of the layered silicate compound in the first sealing resin layer 11 is preferably 5.5 mass% or less, more preferably 5 mass% or less. A configuration in which the first sealing resin layer 11 contains 1.2 mass% or more and 5.5 mass% or less of the layered silicate compound is suitable for increasing the viscosity of the first sealing resin layer 11 and for causing the first sealing resin layer 11 to exhibit thixotropic properties in which the viscosity is lower when the first sealing resin layer 11 is subjected to a pressing force than when the first sealing resin layer 11 is not subjected to the pressing force.

[0046] The first inorganic filler is an inorganic filler other than layered silicate compounds, and examples thereof include silicon compounds (silicon compounds other than layered silicate compounds) such as silica and silicon nitride, and silicate compounds other than layered silicate compounds such as orthosilicate, sorosilicate, and inosilicate. Examples of the first inorganic filler include aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whisker, and boron nitride. The first inorganic filler may be used alone or in combination of two or more. As the first inorganic filler, a silicon compound other than layered silicate compounds is preferably used, and more preferably silica is used.

[0047] The shape of the first inorganic filler can be, for example, a substantially spherical shape, a substantially plate shape, a substantially needle shape, or an irregular shape, and preferably a substantially spherical shape.

[0048] The average value of the maximum length of the first inorganic filler (average particle diameter if the first inorganic filler is substantially spherical) is, for example, 50 μm or less, preferably 20 μm or less, more preferably 10 μm or less. The average value of the maximum length of the first inorganic filler is, for example, 0.1 μm or more, preferably 0.5 μm or more. The average particle diameter of the first inorganic filler is determined, for example, as the D50 value (cumulative 50% median diameter) based on the particle size distribution determined by a particle size distribution measurement method in a laser scattering method.

[0049] The surface of the first inorganic filler may be partially or entirely treated with a surface treatment agent such as a silane coupling agent.

[0050] The content of the first inorganic filler in the first sealing resin layer 11 (i.e., the content of the first inorganic filler in the first thermosetting composition) is preferably 50% by mass or more, more preferably 60% by mass or more. Such a configuration is suitable for suppressing the degree of expansion and contraction due to temperature changes in the first sealing resin layer 11. Moreover, the content of the first inorganic filler in the first sealing resin layer 11 is preferably 90% by mass or less, more preferably 80% by mass or less. Such a configuration is suitable for ensuring the fluidity of the first sealing resin layer 11 in the pressing step described below.

[0051] The first thermosetting composition may contain other components, such as a thermoplastic resin, a pigment, and a silane coupling agent.

[0052] Examples of thermoplastic resins include acrylic resins, natural rubber, butyl rubber, isoprene rubber, chloroprene rubber, ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-acrylic acid ester copolymers, polybutadiene resins, polycarbonate resins, thermoplastic polyimide resins, polyamide resins (such as 6-nylon and 6,6-nylon), phenoxy resins, saturated polyester resins (such as PET), polyamideimide resins, fluororesins, and styrene-isobutylene-styrene block copolymers. These thermoplastic resins may be used alone or in combination of two or more.

[0053] As the thermoplastic resin, from the viewpoint of ensuring compatibility between the thermosetting resin and the thermoplastic resin, an acrylic resin is preferably used.

[0054] Examples of acrylic resins include (meth)acrylic polymers, which are polymers of monomer components including (meth)acrylic acid alkyl esters having a linear or branched alkyl group and other monomers (copolymerizable monomers).

[0055] Examples of the alkyl group of the (meth)acrylic acid alkyl ester include alkyl groups having 1 to 6 carbon atoms, such as methyl, ethyl, propyl, isopropyl, n-butyl, t-butyl, isobutyl, pentyl, and hexyl.

[0056] Examples of the copolymerizable monomer include carboxyl group-containing monomers, acid anhydride monomers, glycidyl group-containing monomers, hydroxyl group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, and acrylonitrile. Examples of the carboxyl group-containing monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of the acid anhydride monomers include maleic anhydride and itaconic anhydride. Examples of the glycidyl group-containing monomers include glycidyl acrylate and glycidyl methacrylate. Examples of the hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. Examples of sulfonic acid group-containing monomers include styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, sulfopropyl(meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid. Examples of phosphoric acid group-containing monomers include 2-hydroxyethylacryloylphosphate. These copolymerizable monomers may be used alone or in combination of two or more.

[0057] The glass transition temperature (Tg) of the thermoplastic resin is, for example, −70° C. or higher. The glass transition temperature is, for example, 0° C. or lower, preferably −5° C. or lower. The glass transition temperature is, for example, a theoretical value calculated by the Fox equation, and a specific calculation method thereof is described in, for example, JP 2016-175976 A.

[0058] The weight average molecular weight of the thermoplastic resin is, for example, 100,000 or more, preferably 300,000 or more. The weight average molecular weight of the thermoplastic resin is, for example, 2 million or less, preferably 1 million or less. The weight average molecular weight of the resin is measured by gel permeation chromatography (GPC) based on a standard polystyrene equivalent value.

[0059] The content of the thermoplastic resin in the first thermosetting composition is, for example, 1% by mass or more, and preferably 2% by mass or more. The content of the thermoplastic resin in the first thermosetting composition is, for example, 80% by mass or less, and preferably 60% by mass or less.

[0060] Examples of the pigment include black pigments such as carbon black. The particle size of the pigment is, for example, 0.001 μm or more. The particle size of the pigment is, for example, 1 μm or less. The particle size of the pigment is an arithmetic mean diameter obtained by observing the pigment with an electron microscope. The content of the pigment in the thermosetting composition is, for example, 0.1 mass % or more. The content is, for example, 2 mass % or less.

[0061] Examples of the silane coupling agent include silane coupling agents containing an epoxy group. Examples of the silane coupling agent containing an epoxy group include 3-glycidoxydialkyldialkoxysilanes such as 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxyalkyltrialkoxysilanes such as 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. As the silane coupling agent, preferably, 3-glycidoxyalkyltrialkoxysilane is used, more preferably, 3-glycidoxypropyltrimethoxysilane is used. The content of the silane coupling agent in the first thermosetting composition is, for example, 0.1% by mass or more, preferably 1% by mass or more. The content of the silane coupling agent in the thermosetting composition is, for example, 10% by mass or less, preferably 5% by mass or less.

[0062] The glass transition temperature of the first sealing resin layer 11 after heat treatment at 150° C. for 1 hour is preferably 135° C. or lower, more preferably 130° C. or lower, and further preferably 125° C. or lower. The glass transition temperature is, for example, 60° C. or higher. The glass transition temperature of the first sealing resin layer 11 can be determined based on the maximum value of the loss tangent (tan δ) in the dynamic viscoelasticity measurement described later in the Examples (the same applies to the glass transition temperature of the second sealing resin layer 12 described later).

[0063] The tensile storage modulus (first tensile storage modulus) at 25°C that the first sealing resin layer 11 has after heat treatment at 150°C for 1 hour is preferably 3.5 GPa or more, more preferably 3.8 GPa or more, and even more preferably 4 GPa or more. The first tensile storage modulus is preferably 9 GPa or less, more preferably 8 GPa or less, and even more preferably 7.7 GPa or less. The value of the tensile storage modulus is a value determined by dynamic viscoelasticity measurement described later in the examples (the same applies to the value of the tensile storage modulus described later).

[0064] The tensile storage modulus of the first sealing resin layer 11 at 100° C. after heat treatment at 150° C. for 1 hour is preferably 0.35 GPa or more, more preferably 0.38 GPa or more, and even more preferably 0.4 GPa or more. The tensile storage modulus is preferably 3 GPa or less, more preferably 2.8 GPa or less, and even more preferably 2.5 GPa or less.

[0065] The elastic modulus at 25° C. measured by a nanoindentation method for the first sealing resin layer 11 after heat treatment at 150° C. for 1 hour is preferably 3.5 GPa or more, more preferably 3.8 GPa or more, and even more preferably 4 GPa or more. The elastic modulus is preferably 9 GPa or less, more preferably 8 GPa or less, and even more preferably 7.7 GPa or less.

[0066] For example, a nanoindenter (trade name "Triboindenter", manufactured by Hysitron) can be used to measure the elastic modulus by nanoindentation (the same applies to the elastic moduli measured by nanoindentation described below). In this measurement, the measurement mode is single indentation measurement, the measurement temperature is 25°C, the indenter used is a Berkovich (triangular pyramid) type diamond indenter, the indenter indentation depth into the measurement object is 300 nm, the indenter indentation speed is 10 nm / sec, and the indenter withdrawal speed from the measurement object is 10 nm / sec. The elastic modulus based on the nanoindentation method is derived by the device used. A specific derivation method is as explained in, for example, Handbook of Micro / nano Tribology (Second Edition) Edited by Bharat Bhushan, CRC Press (ISBN 0-8493-8402-8).

[0067] The elastic modulus at 100° C. measured by a nanoindentation method for the first sealing resin layer 11 after heat treatment at 150° C. for 1 hour is preferably 0.35 GPa or more, more preferably 0.38 GPa or more, and even more preferably 0.4 GPa or more. The tensile storage modulus is preferably 3 GPa or less, more preferably 2.8 GPa or less, and even more preferably 2.5 GPa or less.

[0068] The second sealing resin layer 12 is a layer formed from a thermosetting composition (second thermosetting composition), and in this embodiment, contains at least a thermosetting resin and may contain a second inorganic filler. The second sealing resin layer 12 is in an uncured state (A stage state) or a semi-cured state (B stage state).

[0069] Examples of the thermosetting resin include the thermosetting resins described above for the first thermosetting composition. The content of the thermosetting resin in the second thermosetting composition is preferably 13% by mass or more, more preferably 15% by mass or more. The content of the thermosetting resin in the second thermosetting composition is preferably 35% by mass or less, more preferably 30% by mass or less.

[0070] The thermosetting resin in the second thermosetting composition is preferably an epoxy resin, which is prepared, for example, as an epoxy resin composition containing a base resin, a curing agent, and a curing accelerator.

[0071] Examples of the base agent include the base agents described above for the first thermosetting composition, and preferably a bifunctional epoxy resin is used, more preferably a bisphenol F type epoxy resin. For the second thermosetting composition, the range of the epoxy equivalent of the base agent, the range of the softening point of the base agent, and the range of the ratio of the base agent in the epoxy resin composition are the same as those described above for the first thermosetting composition.

[0072] As the curing agent, as described above with respect to the first thermosetting composition, a phenolic resin is preferably used, and a phenolic novolac resin is more preferably used.

[0073] Regarding the second thermosetting composition, the range of the amount of hydroxyl groups in the phenolic resin, which is the curing agent, relative to one equivalent of epoxy groups in the epoxy resin, which is the base agent, is the same as the range of the amount of hydroxyl groups in the phenolic resin (relative to one equivalent of epoxy groups) described above regarding the first thermosetting composition.

[0074] The curing accelerator may be, for example, the main agent described above for the first thermosetting composition, preferably an imidazole compound, more preferably 2-phenyl-4,5-dihydroxymethylimidazole. The amount of the curing accelerator to be mixed with 100 parts by mass of the main agent is, for example, 0.05 parts by mass or more, and the amount is, for example, 5 parts by mass or less.

[0075] Examples of the second inorganic filler include the first inorganic filler described above in relation to the first thermosetting composition. Preferably, a silicon compound other than a layered silicate compound is used, and more preferably, silica is used.

[0076] The shape of the second inorganic filler may be, for example, approximately spherical, approximately plate-like, approximately needle-like, or irregular, and preferably approximately spherical. The average value of the maximum length of the second inorganic filler (average particle size if the second inorganic filler is approximately spherical) is the same as the average value of the maximum length of the first inorganic filler. The surface of the second inorganic filler may be partially or entirely treated with a surface treatment agent such as a silane coupling agent.

[0077] The content of the second inorganic filler in the second sealing resin layer 12 (i.e., the content of the second inorganic filler in the second thermosetting composition) is preferably 60% by mass or more, more preferably 65% ​​by mass or more, and more preferably 70% by mass or more. Such a configuration is suitable for suppressing the degree of expansion and contraction due to temperature changes in the second sealing resin layer 11. The content of the second inorganic filler in the second sealing resin layer 12 is preferably 90% by mass or less, more preferably 87% by mass or less, and even more preferably 85% by mass or less. Such a configuration is suitable for ensuring the fluidity of the second sealing resin layer 12 in the pressing process described below.

[0078] The second thermosetting composition may contain other components, such as thermoplastic resins, pigments, and silane coupling agents, as described above for the first thermosetting composition.

[0079] The glass transition temperature of the second sealing resin layer 12 after heat treatment at 150° C. for 1 hour is preferably 100° C. or lower, more preferably 95° C. or lower, and further preferably 90° C. or lower. The glass transition temperature is, for example, 60° C. or higher.

[0080] The tensile storage modulus (second tensile storage modulus) of the second sealing resin layer 12 at 100° C. after heat treatment at 150° C. for 1 hour is preferably 0.5 GPa or less, more preferably 0.4 GPa or less, and even more preferably 0.38 GPa or less. The second tensile storage modulus is preferably 0.03 GPa or more, more preferably 0.05 GPa or more, and even more preferably 0.07 GPa or more.

[0081] The tensile storage modulus of the second sealing resin layer 12 at 25° C. after heat treatment at 150° C. for 1 hour is preferably 3 GPa or more, more preferably 4 GPa or more, and even more preferably 5 GPa or more. The tensile storage modulus is preferably 11 GPa or less, more preferably 10 GPa or less, and even more preferably 9 GPa or less.

[0082] The ratio of the second tensile storage modulus (the tensile storage modulus of the second sealing resin layer at 100°C after heat treatment at 150°C for 1 hour) to the first tensile storage modulus (the tensile storage modulus of the first sealing resin layer at 25°C after heat treatment at 150°C for 1 hour) is preferably 0.12 or less, more preferably 0.1 or less, and even more preferably 0.08 or less. The ratio is preferably 0.005 or more, and more preferably 0.01 or more.

[0083] The elastic modulus at 100° C. measured by a nanoindentation method for the second sealing resin layer 12 after heat treatment at 150° C. for 1 hour is preferably 0.5 GPa or less, more preferably 0.4 GPa or less, and even more preferably 0.38 GPa or less. The elastic modulus is preferably 0.03 GPa or more, more preferably 0.05 GPa or more, and even more preferably 0.07 GPa or more.

[0084] The elastic modulus at 25° C. measured by a nanoindentation method for the second sealing resin layer 12 after heat treatment at 150° C. for 1 hour is preferably 3 GPa or more, more preferably 4 GPa or more, and even more preferably 5 GPa or more. The elastic modulus is preferably 11 GPa or less, more preferably 10 GPa or less, and even more preferably 9 GPa or less.

[0085] The encapsulating resin sheet X is produced, for example, by forming a first sealing resin layer 11 and a second sealing resin layer 12, respectively, and then laminating the first sealing resin layer 11 and the second sealing resin layer 12 together. Alternatively, the encapsulating resin sheet X may be produced by forming the first sealing resin layer 11 on a base material, and then forming the second sealing resin layer 12 on the first sealing resin layer 11. Alternatively, the encapsulating resin sheet X may be produced by forming the second sealing resin layer 12 on a base material, and then forming the first sealing resin layer 11 on the second sealing resin layer 12.

[0086] The first sealing resin layer 11 can be formed, for example, as follows. First, the components described above for the first thermosetting composition are mixed in a predetermined ratio to prepare a first thermosetting composition. If necessary, a solvent such as methyl ethyl ketone is further mixed into the composition. Then, the composition is applied onto a substrate such as a release sheet to form a coating film, and the coating film is dried by heating. In this manner, the first sealing resin layer 11 having a sheet shape and in a semi-cured state can be formed.

[0087] The second sealing resin layer 12 can be formed, for example, as follows. First, the components described above for the second thermosetting composition are mixed in a predetermined ratio to prepare a second thermosetting composition. If necessary, a solvent such as methyl ethyl ketone is further mixed into the composition. Then, the composition is applied onto a substrate such as a release sheet to form a coating film, and the coating film is dried by heating. In this manner, the second sealing resin layer 12 having a sheet shape and in a semi-cured state can be formed.

[0088] The first sealing resin layer 11 and the second sealing resin layer 12 thus formed are, for example, bonded together to produce a sealing resin sheet X.

[0089] In the sealing resin sheet X, the first sealing resin layer 11 has a thickness of, for example, 10 μm or more, preferably 25 μm or more, and more preferably 30 μm or more. The first sealing resin layer 11 has a thickness of, for example, 3000 μm or less, preferably 1000 μm or less, more preferably 500 μm or less, further preferably 300 μm or less, and particularly preferably 100 μm or less.

[0090] The thickness of the second sealing resin layer 12 is, for example, 10 μm or more, preferably 30 μm or more, and more preferably 50 μm or more. The thickness of the second sealing resin layer 12 is, for example, 3000 μm or less, preferably 1000 μm or less, and more preferably 500 μm or less.

[0091] The ratio of the thickness of the second sealing resin layer 12 to the thickness of the first sealing resin layer 11 is preferably 0.4 or more, more preferably 0.7 or more, and even more preferably 1 or more. The ratio is preferably 12 or less, more preferably 11 or less, and even more preferably 10 or less.

[0092] The thickness of the encapsulating resin sheet X is, for example, 20 μm or more, preferably 30 μm or more, and more preferably 50 μm or more. The thickness of the encapsulating resin sheet X is, for example, 6000 μm or less, preferably 3000 μm or less, more preferably 1500 μm or less, further preferably 1000 μm or less, particularly preferably 500 μm or less, and most preferably 300 μm or less.

[0093] The sealing resin sheet X has a warpage recovery rate R represented by the following formula (1) of 80% or more, preferably 82% or more, in a warpage recovery evaluation test in which the following first treatment, first measurement, second treatment, and second measurement are performed.

[0094] First treatment: A laminate sample including a 42 alloy plate measuring 90 mm x 90 mm x 150 μm thick and a sealing resin sheet X bonded to the entire surface of one side of the 42 alloy plate in the thickness direction is heated at 150°C for 1 hour and then allowed to stand at 25°C for 1 hour. First measurement: The maximum distance between the surface on which the laminate sample is placed with the 42 alloy plate of the laminate sample facing down and the edge of the laminate sample is measured as the first warping length D1. Second treatment: The laminate sample is placed on the surface of a heating plate at 100° C. for 1 minute. Second measurement: The maximum distance between the surface of the heating plate and the edge of the laminate sample (the maximum vertical distance between the surface of the heating plate and the underside of the edge of the laminate sample when the laminate sample is curved in such a way that the edge of the laminate sample rises up from the heating plate) is measured as the second warping length D2.

[0095] Formula (1): R=[(D1-D2) / D1]×100

[0096] The second warpage length D2 is preferably 2 mm or less, more preferably 1.8 mm or less, and further preferably 1.5 mm or less.

[0097] The warp recovery rate R is preferably 120% or less, more preferably 110% or less. When the warp length D2 is a negative value, the warp recovery rate R exceeds 100%. When the laminate sample is curved in such a manner that an inner region surrounded by the entire periphery of the edge of the laminate sample rises up from the heating plate during the second measurement, the maximum vertical distance between the lower surface of the inner region and the surface of the heating plate, with a negative sign added, is defined as the second warp length D2.

[0098] The encapsulating resin sheet X has a penetration length L of preferably 50 μm or less, more preferably 30 μm or less, as shown in a penetration length evaluation test in which the following first to fourth steps are carried out. The penetration length L is preferably 0 μm or more.

[0099] First step: A dummy chip mounting substrate is prepared, the substrate comprising a glass substrate and a dummy chip measuring 3 mm x 3 mm x 200 μm thick, the dummy chip being bonded to the glass substrate via bumps in a state facing the glass substrate with a gap therebetween, and the length from the glass substrate to the dummy chip in the gap being 20 μm. Second step: With the first sealing resin layer 11 side of the sealing resin sheet X in contact with the dummy chip on the glass substrate, the sealing resin sheet X is pressed toward the glass substrate by a vacuum platen press under the conditions of a temperature of 65° C., a vacuum degree of 1.6 kPa or less, a pressure of 0.1 MPa, and a pressure time of 40 seconds, so that the open edge of the gap is closed by the first sealing resin layer 11 that is in close contact with the glass substrate around the dummy chip. Third step: After the second step, the sealing resin sheet X is thermally cured by heating at 150° C. for 1 hour under atmospheric pressure. Fourth step: After the third step, the penetration length L of the sealing resin sheet X into the gap is measured.

[0100] FIG. 2 shows a method for sealing an electronic component chip on a substrate using a sealing resin sheet X.

[0101] In this method, first, as shown in FIG. 2A, a sealing resin sheet X is prepared (preparation step).

[0102] Next, as shown in FIG. 2B, the workpiece W and the sealing resin sheet X are placed between a first press plate P1 and a second press plate P2 provided in a flat plate press (placement step).

[0103] The workpiece W includes a substrate S and a plurality of chips 21. The substrate S is a base material that is later divided into single mounting substrates, and has a mounting surface Sa. The mounting surface Sa is provided with a terminal for mounting (not shown). The chip 21 is an electronic component chip such as a semiconductor chip, and has a main surface 21a and a side surface 21b. The main surface 21a is provided with a terminal for external connection (not shown). The chip 21 is mounted on the substrate S via bump electrodes 22 in a state facing the substrate S across a gap G. Each bump electrode 22 is interposed between a terminal provided on the mounting surface Sa of the substrate S and a terminal provided on the main surface 21a of the chip 21, and electrically connects the substrate S and the chip 21.

[0104] The distance between the substrate S and the chip 21 is, for example, 10 μm or more, preferably 13 μm or more, and more preferably 15 μm or more. The distance is, for example, 60 μm or less, preferably 55 mm or less, and more preferably 50 μm or less.

[0105] The multiple chips 21 are mounted on the mounting surface Sa of the substrate S at intervals in the planar direction. The interval between adjacent chips 21 is, for example, 50 μm or more, preferably 100 μm or more, and more preferably 200 μm or more. The interval between adjacent chips 21 is, for example, 10 mm or less, preferably 5 mm or less, and more preferably 1 mm or less.

[0106] In this step, the work W is placed on the first press plate P1 so that the substrate S of the work W contacts the first press plate P1. The sealing resin sheet X is laminated on the work W so that the first sealing resin layer 11 of the work W contacts the chip 21 of the work W.

[0107] 2C, the encapsulating resin sheet X and the workpiece W are pressed in the thickness direction by a first press plate P1 and a second press plate P2 (pressing step). Specifically, in a state where the first encapsulating resin layer 11 side of the encapsulating resin sheet X contacts the chip 21 on the substrate S, the encapsulating resin sheet X is pressed toward the substrate S while being softened by heating.

[0108] The pressing pressure is, for example, 0.01 MPa or more, preferably 0.05 MPa or more. The pressing pressure is, for example, 10 MPa or less, preferably 5 MPa or less. The pressing time is, for example, 0.3 minutes or more, preferably 0.5 minutes or more. The pressing time is, for example, 10 minutes or less, preferably 5 minutes or less. The heating temperature during pressing is, for example, 40°C or more, preferably 60°C or more. The heating temperature is, for example, 100°C or less, preferably 95°C or less.

[0109] In this process, the sealing resin sheet X, while maintaining the B stage, deforms in accordance with the outer shape of the chips 21, covers the side surfaces 21b of each chip 21, and comes into contact with the mounting surface Sa of the substrate S that does not overlap with the chips 21 in a plan view. The open edge of the gap G is closed by the first sealing resin layer 11 that is in close contact with the substrate S around the chips 21.

[0110] The configuration in which the first sealing resin layer 11 contains a layered silicate compound is suitable for increasing the viscosity of the first sealing resin layer 11 and for causing the first sealing resin layer 11 to exhibit thixotropic properties in which the viscosity is lower when the first sealing resin layer 11 is subjected to a pressing force than when the first sealing resin layer 11 is not subjected to the pressing force, as described above. Therefore, the sealing resin sheet X is suitable for the first sealing resin layer 11 together with the second sealing resin layer 12 to soften and flow under the pressing force in this step and to deform to follow the external shape of the chip 21.

[0111] The deformed encapsulating resin sheet X is allowed to slightly penetrate into the gap G between the substrate S and the chip 21. Specifically, the encapsulating resin sheet X is allowed to have a penetration length L' (see FIG. 3C) into the gap G based on the side surface 21b of the chip 21. The penetration length L' is preferably 50 μm or less, more preferably 30 μm or less. The penetration length L' is preferably -20 μm or more, more preferably -10 μm or more, and even more preferably -5 μm or more.

[0112] Next, the workpiece W sealed with the sealing resin sheet X is removed from the flat plate press, and then, as shown in FIG. 2D, the sealing resin sheet X is heated and cured (curing step).

[0113] The heating temperature (cure temperature) is, for example, 100° C. or higher, preferably 120° C. or higher. The heating temperature (cure temperature) is, for example, 200° C. or lower, preferably 180° C. or lower. The heating time is, for example, 10 minutes or longer, preferably 30 minutes or longer. The heating time is, for example, 180 minutes or shorter, preferably 120 minutes or shorter.

[0114] In the curing step, since the first sealing resin layer 11 contains a layered silicate compound, a decrease in viscosity caused by a rise in temperature is suppressed, and further penetration into the voids G is suppressed. In contrast, the viscosity of the second sealing resin layer 12 decreases once before curing and the second sealing resin layer 12 becomes fluid, and the exposed surface opposite to the first sealing resin layer 11 is flattened.

[0115] The penetration length L (see FIG. 3D) of the cured encapsulating resin sheet X into the gap G is preferably 50 μm or less, more preferably 30 μm or less. The penetration length L is preferably 0 μm or more.

[0116] Next, for each electronic component chip, surface processing such as laser printing (printing by laser marking) is performed on the surface of the sealing resin (hardened sealing resin sheet X).

[0117] Thereafter, the hardened sealing resin sheet X and the substrate S are cut along predetermined cutting lines by blade dicing, and are separated into individual electronic component chip resin-sealed bodies.

[0118] In the encapsulating resin sheet X, the warp recovery rate R shown in the above-mentioned warp recovery evaluation test is, as described above, 80% or more, preferably 82% or more, and preferably 120% or less, more preferably 110% or less. Such a configuration is suitable for suppressing the height difference of the work surface in the manufacturing process of the electronic component chip resin encapsulation body using the encapsulating resin sheet X. Suppressing the height difference of the work surface is suitable for performing surface processing such as laser printing for each electronic component chip on the encapsulating resin surface of the work with high accuracy over the entire work.

[0119] In the encapsulating resin sheet X, the second warpage length D2 shown in the above-mentioned warpage recovery evaluation test is, as described above, preferably 2 mm or less, more preferably 1.8 mm or less, and further preferably 1.5 mm or less. Such a configuration is suitable for precisely processing the surface of the encapsulating resin (the encapsulating resin sheet X after curing) by suppressing the height difference on the surface of the work W in the manufacturing process of the electronic component chip resin encapsulation body using this encapsulating resin sheet.

[0120] In the pressing step described above with reference to FIG. 2C, the second sealing resin layer 12 of the sealing resin sheet X is fluidized by the pressing force, and the exposed surface opposite to the first sealing resin layer 11 is flattened. In the pressing step, the sealing resin sheet X is suitable for the first sealing resin layer 11 together with the second sealing resin layer 12 to be softened and fluidized by the pressing force, and to deform to follow the outer shape of the electronic component chip, as described above. In such a pressing step, a part of the sealing resin sheet X is allowed to slightly enter the gap G between the substrate S and the chip 21. In the curing step described above with reference to FIG. 2D, the first sealing resin layer 11 is suppressed from fluidizing due to a decrease in viscosity caused by a rise in temperature, and excessive penetration into the gap G is suppressed, as described above. That is, the sealing resin sheet X is suitable for controlling the length of the sealing resin entering the gap G between the substrate S and the chip 21 in the manufacturing process of the electronic component chip resin sealing body.

[0121] In the sealing resin sheet X, as described above, the first sealing resin layer 11 has a tensile storage modulus at 25° C. (first tensile storage modulus) after heat treatment at 150° C. for 1 hour of preferably 3.5 GPa or more, more preferably 3.8 GPa or more, and further preferably 4 GPa or more. Such a configuration is suitable for suppressing damage such as cracks and chipping from occurring in the base material on which the electronic component chips are mounted when the electronic component chips are singulated by blade dicing in the process of producing the electronic component chip resin sealing body using the sealing resin sheet X.

[0122] In the encapsulating resin sheet X, as described above, the glass transition temperature of the second encapsulating resin layer 12 after heat treatment at 150° C. for 1 hour is preferably 100° C. or lower, more preferably 95° C. or lower, and further preferably 90° C. or lower. This configuration is suitable for reducing warping of the encapsulating resin sheet X after heat curing by temporarily softening the encapsulating resin sheet by heating it to about 100° C. when the sheet is warped.

[0123] In the encapsulating resin sheet X, as described above, the tensile storage modulus at 100° C. (second tensile storage modulus) of the second encapsulating resin layer 12 after heat treatment at 150° C. for 1 hour is preferably 0.5 GPa or less, more preferably 0.4 GPa or less, and further preferably 0.38 GPa or less. This configuration is suitable for reducing warpage of the encapsulating resin sheet X after heat curing by temporarily softening the encapsulating resin sheet by heating it to about 100° C. when the sheet is warped.

[0124] In the sealing resin sheet X, as described above, the ratio of the second tensile storage modulus to the first tensile storage modulus is preferably 0.12 or less, more preferably 0.1 or less, and further preferably 0.08 or less. Such a configuration is suitable for achieving both the suppression of the warpage and the suppression of the damage.

[0125] In the encapsulating resin sheet X, as described above, the ratio of the thickness of the second encapsulating resin layer 12 to the thickness of the first encapsulating resin layer 11 is preferably 0.4 or more, more preferably 0.7 or more, and even more preferably 1 or more. Such a configuration is suitable for controlling the penetration length of the encapsulating resin into the gap G between the substrate S and the electronic component chip 21 in the manufacturing process of the electronic component chip resin encapsulated body including the pressing step and the curing step as described above in which the encapsulating resin sheet X is used.

[0126] In the encapsulating resin sheet X, the first encapsulating resin layer 11 and the second encapsulating resin layer 12 preferably contain an epoxy resin, and the softening point of the epoxy resin is preferably 50° C. or higher, more preferably 60° C. or higher, even more preferably 72° C. or higher, particularly preferably 75° C. or higher, and is preferably 130° C. or lower, more preferably 110° C. or lower, and even more preferably 90° C. or lower. Such a configuration is suitable for ensuring the fluidity of the first and second encapsulating resin layers in the pressing step, and is therefore useful for shortening the time of the pressing step and for flattening the exposed surface of the second encapsulating resin layer (the surface of the second encapsulating resin layer opposite to the first encapsulating resin layer) in the pressing step.

[0127] In the encapsulating resin sheet X, the first encapsulating resin layer 11 and the second encapsulating resin layer 12 preferably contain a phenol resin together with an epoxy resin. Such a configuration is suitable for the present encapsulating resin sheet to exhibit high heat resistance and high chemical resistance after curing, and is therefore suitable for forming an encapsulating material with excellent encapsulation reliability.

[0128] In the present invention, the encapsulating resin sheet X may have a single-layer structure of the first encapsulating resin layer 11 without including the second encapsulating resin layer 12 . EXAMPLES

[0129] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, the specific numerical values ​​of the blending amount (content), physical property values, parameters, etc. used in the following description can be replaced with the upper limit (a numerical value defined as "not more than" or "less than") or lower limit (a numerical value defined as "not less than" or "exceeding") of the corresponding blending amount (content), physical property values, parameters, etc. described in the above "Form for carrying out the invention".

[0130] [Preparation Examples 1 to 5] Each of the first resin films of Preparation Examples 1 to 5 for forming a first sealing resin layer was prepared as follows. First, the components were mixed according to the formulation shown in Table 1 to prepare a composition (varnish) (in Table 1, the units of the numerical values ​​expressing the composition are relative "parts by mass"). Next, the composition was applied to a 50 μm-thick polyethylene terephthalate film (PET film) whose surface had been subjected to silicone release treatment to form a coating film. Next, this coating film was heated and dried at 120° C. for 2 minutes to form a 50 μm-thick first resin film on the PET film (the formed first resin film was in a B-stage state).

[0131] [Preparation Examples 6 to 9] Each of the second resin films of Preparation Examples 6 to 9 for forming the second sealing resin layer was prepared as follows. First, the components were mixed according to the formulation shown in Table 2 to prepare a composition (varnish) (in Table 2, the units of the numerical values ​​expressing the composition are relative "parts by mass"). Next, the composition was applied to a 50 μm-thick PET film whose surface was treated with silicone release to form a coating film. Next, this coating film was heated and dried at 120° C. for 2 minutes to form a 52.5 μm-thick resin film on the PET film (the formed resin film was in a B-stage state). Then, four 52.5 μm-thick resin films formed as described above from the varnish of the same composition were bonded together to prepare a 210 μm-thick second resin film.

[0132] [Table 1]

[0133] [Table 2]

[0134] The components used in Preparation Examples 1 to 9 are as follows. Epoxy resin E1: "YSLV-80XY" manufactured by Nippon Steel Chemical Co., Ltd. (bisphenol F type epoxy resin, high molecular weight epoxy resin, epoxy equivalent 200g / eq., solid at room temperature, softening point 80℃) Epoxy resin E2: DIC's "EPICLON EXA-4850-150" (bisphenol A type epoxy resin, molecular weight 900, epoxy equivalent 450g / eq., liquid at room temperature) Phenolic resin F1: Gun-ei Chemical's "LVR-8210DL" (novolac type phenolic resin, latent hardener, hydroxyl equivalent 104g / eq., solid at room temperature, softening point 60°C) Phenolic resin F2: Meiwa Kasei's "MEHC-7851SS" (phenol aralkyl resin, latent hardener, hydroxyl equivalent 201-220g / eq., solid at room temperature, softening point 64-85°C) Acrylic resin: "HME-2006M" manufactured by Negami Chemical Industries Co., Ltd. (acrylic resin containing carboxyl groups, acid value 32 mg KOH / g, weight average molecular weight 1.29 million, glass transition temperature (Tg) -13.9°C, methyl ethyl ketone solution with solid content concentration of 20% by mass) Silane coupling agent: Shin-Etsu Chemical's "KBM-403" (3-glycidoxypropyltrimethoxysilane) Layered silicate compound: "Esben NX" manufactured by Hojun Co., Ltd. (organic bentonite whose surface is modified with dimethyl distearyl ammonium) Inorganic filler f1: "FB-8SM" manufactured by Denka Co., Ltd. (spherical silica particles, average particle size 7.0 μm, no surface treatment) Inorganic filler f2: Admatechs' "SC220G-SMJ" (silica particles, average particle size 0.5 μm) surface-treated with 3-methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical's "KBM-503") (the silane coupling agent used for surface treatment was 1 part by mass per 100 parts by mass of silica particles). Curing accelerator: "2PHZ-PW" (2-phenyl-4,5-dihydroxymethylimidazole) manufactured by Shikoku Chemical Industry Co., Ltd. Solvent: methyl ethyl ketone (MEK) Carbon black: Mitsubishi Chemical #20, average particle size 50 nm

[0135] [Examples 1 to 4, Comparative Examples 1 to 3] Each of the encapsulating resin sheets was produced in Examples 1 to 4 and Comparative Examples 1 to 3. Specifically, a first resin film (first encapsulating resin layer) and a second resin film (second encapsulating resin layer) were bonded together in the combination shown in Table 3 to produce an encapsulating resin sheet having a thickness of 260 μm.

[0136] <Measurement of Tensile Storage Modulus> The tensile storage modulus at 25°C and the tensile storage modulus at 100°C were measured by dynamic viscoelasticity measurement for the first encapsulating resin layer after curing and the second encapsulating resin layer after curing of each of the encapsulating resin sheets of Examples 1 to 4 and Comparative Examples 1 to 3. A dynamic viscoelasticity measuring device (product name "RSA-G2", manufactured by TA Instruments) was used for the measurement. The sample pieces for measurement (sample pieces of the first encapsulating resin layer and sample pieces of the second encapsulating resin layer) were cured by heat treatment at 150°C for 1 hour and had a size of 10 mm wide x 40 mm long. In the measurement, the initial chuck distance of the chucks for holding the sample pieces was 20 mm, the measurement mode was a tension mode, the measurement temperature range was -10°C to 260°C, the heating rate was 10°C / min, the frequency was 1 Hz, and the dynamic strain was 0.05%. The tensile storage modulus M1 (first tensile storage modulus) at 25° C. and the tensile storage modulus M1' at 100° C. measured for the first encapsulating resin layer after curing, and the tensile storage modulus M2 at 25° C. and the tensile storage modulus M2' (second tensile storage modulus) at 100° C. measured for the second encapsulating resin layer after curing are shown in Table 3. Table 3 also shows the ratio of the tensile storage modulus M2' to the tensile storage modulus M1 (M2' / M1), and the ratio of the tensile storage modulus M2 to the tensile storage modulus M2' (M2 / M2').

[0137] <Measurement of Glass Transition Temperature> The glass transition temperatures of the first sealing resin layer after curing and the second sealing resin layer after curing in each of the sealing resin sheets of Examples 1 to 4 and Comparative Examples 1 to 3 were determined from the maximum value of the loss tangent (tan δ) measured using dynamic viscoelasticity measurement. The sample pieces for measurement (sample pieces of the first sealing resin layer, sample pieces of the second sealing resin layer) were cured by heat treatment at 150°C for 1 hour. For the measurement, a dynamic viscoelasticity measurement device (product name "RSA-G2", manufactured by TA Instruments) was used (the measurement conditions were the same as those described above for the measurement of the tensile storage modulus). The results are shown in Table 3.

[0138] <Evaluation of penetration length> For each of the sealing resin sheets of Examples 1 to 4 and Comparative Examples 1 to 3, the penetration length into the gap between the substrate and the electronic component chip was measured after the resin sheets had been cured to seal an electronic component chip mounted on a substrate with the electronic component chip facing the substrate via a gap.

[0139] First, a sample sheet X' having a length of 10 mm, a width of 10 mm, and a thickness of 150 μm was prepared from the sealing resin sheet of each Example and Comparative Example, as shown in Fig. 3A. The sample sheet X' includes a first sealing resin layer 11 and a second sealing resin layer 12 in this order in the thickness direction.

[0140] Meanwhile, a dummy chip mounting substrate was prepared as the workpiece W (first step). The dummy chip mounting substrate includes a glass substrate S and a dummy chip 21' measuring 3 mm × 3 mm × 200 μm thick, with the dummy chip 21' facing the substrate S across a gap G and bonded to the substrate S via bumps 22, and the length from the substrate S to the dummy chip 21' in the gap G is 20 μm.

[0141] Next, as shown in FIG. 3B, the above-mentioned workpiece W and sample sheet X' were placed between a first press plate P1 and a second press plate P2 of a flat plate press.

[0142] Next, as shown in FIG. 3C, the dummy chip 21' on the substrate S was sealed with the sample sheet X' by a vacuum platen press under sealing conditions of a temperature of 65° C., a vacuum degree of 1.6 kPa or less, a pressure of 0.1 MPa, and a pressure time of 40 seconds (second step).

[0143] Next, as shown in FIG. 3D, the sample sheet X′ was cured by heating at 150° C. for 1 hour under atmospheric pressure (third step).

[0144] Then, as shown in the enlarged view of Fig. 3D, using side surface 21b' of dummy chip 21' as a reference, the length of penetration of the sealing resin (part of first sealing resin layer 11) derived from sample sheet X' from side surface 21b' into gap G between dummy chip 21' and substrate S was measured as penetration length L (fourth step). The results are shown in Table 3 (a negative value for penetration length L means that a space (see thick dashed line in Fig. 3D) is formed that protrudes outward from side surface 21b' of dummy chip 21'. The absolute value of the "negative" value corresponds to the protruding length of that space).

[0145] <Warpage evaluation> The following first treatment, first measurement, second treatment, and second measurement were carried out in this order.

[0146] First, in the first treatment, a laminate sample comprising a 42 alloy plate measuring 90 mm x 90 mm x 150 μm in thickness and a sealing resin sheet bonded to the entire surface of one side of the 42 alloy plate in the thickness direction was heated at 150°C for 1 hour and then left to stand at 25°C for 1 hour.

[0147] Next, in the first measurement, the maximum distance between the surface on which the laminate sample was placed with the 42 alloy plate of the laminate sample facing downward and the edge of the laminate sample was measured as the warp length D1.

[0148] Next, in the second treatment, the laminate sample was left standing on the surface of a heating plate at 100° C. for 1 minute.

[0149] Next, in the warpage measurement, the maximum distance between the surface of the heating plate and the edge of the laminate sample was measured as the warpage length D2. The results are shown in Table 3. Table 3 also shows the warpage recovery rate R (%), which is expressed by the following formula (1).

[0150] Formula (1): R=[(D1-D2) / D1]×100

[0151] <Damage to the circuit board> For each of the encapsulating resin sheets of Examples 1 to 4 and Comparative Examples 1 to 3, the effect of suppressing damage to a substrate was examined as follows.

[0152] First, a sample workpiece was prepared by bonding an encapsulating resin sheet (260 μm thick) of the same size to an alumina substrate of 100 mm × 100 mm × 200 μm in size. Specifically, the encapsulating resin sheet was bonded to the entire surface of one side of the alumina substrate in the thickness direction using a vacuum platen press under the following conditions: temperature 65°C, vacuum level 1.6 kPa or less, pressure 0.1 MPa, and pressure time 40 seconds.

[0153] Next, the sample workpiece was heated at 150° C. for 1 hour under atmospheric pressure to harden the sealing resin sheet in the sample workpiece.

[0154] Next, the sample work was cut into individual pieces of 1 mm x 1 mm size by blade dicing using a dicing device (product name "DFD651", manufactured by Disco Corporation) and a dicing blade (product name "GIA850", manufactured by Disco Corporation), to obtain multiple sample pieces. In this dicing, the rotation speed of the dicing blade was set to 30,000 rpm.

[0155] Next, the side of the substrate of each sample piece was observed under an optical microscope to check for damage such as cracks and chipping in the substrate (30 sample pieces were observed). Of the 30 sample pieces observed, the number of sample pieces with damaged substrates is shown in Table 3.

[0156] [Table 3] [Explanation of symbols]

[0157] X Sealing resin sheet 11 First sealing resin layer 12 Second sealing resin layer W work S-substrate Sa mounting surface 21 Chips 21a Main surface 21b Side 22 Bump electrode P1 First press plate P2 Second press plate

Claims

1. A sealing resin sheet containing a thermosetting resin, the encapsulating resin sheet includes a first encapsulating resin layer and a second encapsulating resin layer in this order in a thickness direction, the first sealing resin layer contains a first thermosetting resin, a layered silicate compound, and a first inorganic filler; the second sealing resin layer contains a second thermosetting resin and a second inorganic filler; A sealing resin sheet characterized in that, in a warp recovery evaluation test in which the following first treatment, first measurement, second treatment, and second measurement are carried out in this order, a warp recovery rate R represented by the following formula (1) is 80% or more. First treatment: A laminate sample comprising a 42 alloy plate measuring 90 mm x 90 mm x 150 μm thick and the sealing resin sheet bonded to the entire thickness of one side of the 42 alloy plate is heated at 150°C for 1 hour and then left to stand at 25°C for 1 hour. First measurement: The maximum distance between the surface on which the laminate sample is placed with the 42 alloy plate of the laminate sample facing downward and the edge of the laminate sample is measured as the first warpage length D1. Second treatment: The laminate sample is left standing on the surface of a heating plate at 100° C. for 1 minute. Second measurement: The maximum distance between the surface of the heating plate and the edge of the laminate sample is measured as a second warpage length D2. Formula (1): R=[(D1-D2) / D1]×100

2. The sealing resin sheet according to claim 1 , wherein the second warpage length D2 is 2 mm or less.

3. 3. The encapsulating resin sheet according to claim 1, wherein the penetration length L shown in a penetration length evaluation test in which the following first to fourth steps are performed is 0 μm or more and 50 μm or less. First step: A dummy chip mounting substrate is prepared, which includes a glass substrate and a dummy chip measuring 3 mm x 3 mm x 200 μm thick, the dummy chip being bonded to the glass substrate via bumps in a state where the dummy chip faces the glass substrate with a gap therebetween, and the length from the glass substrate to the dummy chip in the gap is 20 μm. Second step: With the first sealing resin layer side of the sealing resin sheet in contact with the dummy chip on the glass substrate, the sealing resin sheet is pressed toward the glass substrate using a vacuum flat press under conditions of a temperature of 65°C, a vacuum degree of 1.6 kPa or less, a pressure of 0.1 MPa, and a pressing time of 40 seconds, and the open edge of the gap is closed by the first sealing resin layer that is in close contact with the glass substrate around the dummy chip. Third step: After the second step, the sealing resin sheet is cured by heating at 150° C. for 1 hour under atmospheric pressure. Fourth step: After the third step, the penetration length L of the sealing resin sheet into the gap is measured.

4. 4. The sealing resin sheet according to claim 1, wherein the first sealing resin layer has a first tensile storage modulus of 3.5 GPa or more at 25°C after heat treatment at 150°C for 1 hour.

5. 5. The sealing resin sheet according to claim 1, wherein the second sealing resin layer has a glass transition temperature of 100°C or lower after heat treatment at 150°C for 1 hour.

6. 6. The sealing resin sheet according to claim 1, wherein the second sealing resin layer has a second tensile storage modulus of 0.5 GPa or less at 100°C after heat treatment at 150°C for 1 hour.

7. 7. The sealing resin sheet according to claim 1, wherein a ratio of a second tensile storage modulus at 100°C of the second sealing resin layer after heat treatment at 150°C for 1 hour to a first tensile storage modulus at 25°C of the first sealing resin layer after heat treatment at 150°C for 1 hour is 0.12 or less.

Citation Information

Patent Citations

  • Epoxy resin composition for semiconductor sealing

    JP2001181481A

  • Semiconductor light-emitting apparatus and method of manufacturing the same

    JP2009135485A

  • Encapsulation resin sheet, semiconductor device using the same and manufacturing method of semiconductor device

    JP2012169414A

  • Resin sheet for sealing electronic component, resin-sealed semiconductor device, and method for manufacturing resin-sealed semiconductor device

    JP2014036097A

  • Semiconductor device manufacturing method

    JP2015220350A